Vanadian and chromian garnet- and epidote-supergroup minerals in metamorphosed Paleozoic black shales from Čierna Lehota, Strážovské vrchy Mountains, Slovakia: crystal chemistry and evolution. (21st August 2018) - Bačík, Peter; Uher, Pavel; Kozáková, Petra; Števko, Martin; Ozdín, Daniel; Vaculovič, Tomáš
Abstract: Silicate minerals enriched in V, Cr and Mn including garnets and epidote-supergroup members, in association with amphiboles, albite, hyalophane, titanite, chamosite, sulfides and other minerals occur in Devonian black shales near Čierna Lehota in the Strážovské vrchy Mountains, Slovakia. The garnets have high concentrations of V, Cr and Mn (up to 17 wt.% V2 O3, ≤11 wt.% Cr2 O3 and ≤ 21 wt.% MnO) and several compositional types. Vanadian-chromian grossular (Grs 1) usually preserves primary metamorphic oscillatory zoning, whereas solid solutions between goldmanite (Gld 2A, B), V- and Cr-rich grossular and spessartine (Grs 2A, B, Sps 2) form irregular domains or crystals with variable zoning. Dominant substitutions in the garnets include CaMn–1 and (V, Cr)Al–1, resulting in coupled Ca(V, Cr)Mn–1 Al–1 . Epidote-supergroup minerals occur as abundant anhedral crystals with variable compositional zoning. Nearly all crystals have a complete zoning sequence beginning with REE -rich allanite-(La), followed by mukhinite and by V- and Cr-rich clinozoisite to mukhinite and V- and Cr-poor clinozoisite. In common with garnets, the epidote-supergroup minerals are enriched in V, Cr and Mn (<7 wt.% V2 O3, <5 wt.% Cr2 O3 and <3 wt.% MnO). Lanthanum is the dominant REE (up to 11.5 wt.% La2 O3 ) in allanite-(La). The composition of epidote-supergroup minerals is controlled by REE Fe 2+ (CaAl)–1, REE Mg(CaAl)–1, REE Mn 2+ (CaAl)–1 and REE Fe 2+ (CaFe 3+ )–1 substitutions introducing REE, together with VAl–1 and CrAl–1 substitutions. The negative Ce and slightly positive Eu anomalies displayed in chondrite-normalized patterns and enrichment in V, Cr and Mn are ascribed to the geochemical properties of the protolith. The minerals investigated exhibit multi-stage evolution: (1) presumed low-grade greenschist-facies metamorphism; and (2) development of V- and Cr-rich zones in both garnet- and epidote-supergroup minerals which result from late-Variscan contact metamorphism due to granitic intrusion of the Suchý Massif. Decreased temperature following the metamorphic peak probably resulted in the formation of REE -, V- and Cr-poor clinozoisite and secondary garnet.